2021
DOI: 10.1177/1535370220983235
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for lymphatics in acute kidney injury: Beneficial or maleficent?

Abstract: Acute kidney injury, a sudden decline in renal filtration, is a surprisingly common pathology resulting from ischemic events, local or systemic infection, or drug-induced toxicity in the kidney. Unchecked, acute kidney injury can progress to renal failure and even recovered acute kidney injury patients are at an increased risk for developing future chronic kidney disease. The initial extent of inflammation, the specific immune response, and how well inflammation resolves are likely determinants in acute kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Lymphangiogenesis has been demonstrated in multiple models of renal injury (Creed & Rutkowski, 2021 ; Zarjou et al, 2019 ). To determine whether proteinuric injury following podocyte loss induced renal lymphangiogenesis, LYVE‐1, and podoplanin immunolabeling were performed and quantified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lymphangiogenesis has been demonstrated in multiple models of renal injury (Creed & Rutkowski, 2021 ; Zarjou et al, 2019 ). To determine whether proteinuric injury following podocyte loss induced renal lymphangiogenesis, LYVE‐1, and podoplanin immunolabeling were performed and quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to these findings, our study identified a significant increase in lymphatic density in response to a progressive proteinuric kidney injury or IRI by day 7 post‐injury. Lymphatic vessels and renal lymphangiogenesis following kidney injury have been reported to be beneficial in some models by reducing fibrosis and increasing functional recovery, while others have reported detrimental injury outcomes due to lymphatic propagation of a pro‐inflammatory innate immune response (Creed & Rutkowski, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For whole-mount imaging, kidneys from C57BL6/J mice were prepared by cardiac perfusion with warm saline, perfusion fixation with 37°C 1% paraformaldehyde, followed by postfixation overnight at 4°C in 3% paraformaldehyde. For whole-mount immunohistochemistry, tissues were incubated for 20 minutes in increasing percentage methanol washes (20,40,60, and 100) before permeabilization with a 1:4 (volume/volume) DMSO/methanol solution (Dent's). Tissue bleaching was accomplished with 20minute incubations of ice-cold H 2 O 2 (0.1%, 0.3%, and 1% in Dent's solution).…”
Section: Kidney Whole-mount and Idisco Clearingmentioning
confidence: 99%